Differential association of visceral adipose tissue with coronary plaque characteristics in patients with and without diabetes mellitus - Osawa, Kazuhiro (BioMed Central, 2014)
BACKGROUND: Excess visceral adipose tissue (VAT) is closely associated with the presence of coronary artery plaques that are vulnerable to rupture. Patients with diabetes mellitus (DM) have more VAT than patients without DM, but the extent to which VAT contributes to the characteristics of coronary plaques before and after the development of DM is not fully understood. METHODS: We retrospectively evaluated 456 patients (60% male, age 64 ± 16 years) who were suspected to have cardiovascular disease and underwent 64-slice computed tomography angiography (CTA). Seventy-one (16%) patients had vulnerable plaques (CT density < 50 Hounsfield Units, positive remodeling index > 1.05, and adjacent spotty areas of calcification). RESULTS: Patients were divided into tertiles according to the VAT area. There were stepwise increases in noncalcified and vulnerable plaques with increasing tertiles of VAT area in patients without DM, but not in patients with DM. Multivariate analysis showed that a larger VAT area was significantly associated with a higher risk of vulnerable plaque in patients without DM (odds ratio 3.17, 95% confidence interval 1.08–9.31, p = 0.04), but not in patients with DM. CONCLUSIONS: The VAT area is associated with the characteristics of coronary plaques on CTA in patients without DM, but not in patients with DM. VAT may be a significant cardiometabolic risk factor that is associated with plaque vulnerability before the development of DM. CTA findings may help to improve risk stratification in such patients.